Molecular Identification of an Endophytic Fungus Isolated from *Hyssopus Officinalis - L. M., Khayrullaeva (American Journal of Biology and Natural Sciences, 2025)
The biochemical and pharmaceutical industries are increasingly relying on endophytic fungi as a source of novel therapeutic biomolecules. These fungi are capable of producing a wide range of bioactive compounds, including immunosuppressants, anticancer agents, plant growth promoters, antimicrobial agents, insecticides, antioxidants, and antibiotics, presenting great potential for medical applications.